Health media and the management of the krona-coved - 19 pandemic crisis as fake news spreads through social media sites - Khaira Mahammedi (Social Empowerment Journal, 2020)
This paper attempts to shed light on how the health media is addressing the crona-19 pandemic crisis in light of the circulation of fake news through social media sites, which has become a virtual space competing for traditional media through which different types of false and misleading information circulate to the public, and in light of that the study is interested in diagnosing the role of health media in managing the Crona crisis, exploring the most prominent forms of media treatments of the Krona Covid-19 pandemic, and then monitoring the mechanisms and methods of spreading fake news through social media sites, as well as The study concluded that health media should adhere to the principles of media ethics in its treatment and coverage of the pandemic.